Cannabidiol (CBD) in the Self-Treatment of Depression-Exploratory Study and a New Phenomenon of Concern for Psychiatrists - Wieckiewicz, Gniewko; Stokłosa, Iga; Stokłosa, Maciej; Gorczyca, Piotr; Pudlo, Robert (Frontiers in Psychiatry, 2022)
Cannabis sativa, also known as marijuana or marihuana, is a recreational plant that contains many 8 chemicals that are constantly being studied by scientists around the world. One of these substances is 9 cannabidiol (CBD), which has gained widespread popularity on the internet as a cure for mental 10 health problems, leading many people to use CBD to self-treat depression and anxiety. This article 11 presents an exploratory cohort study (n = 90) of a group of people aged 16-69 using CBD to self-heal 12 depression symptoms. The survey included basic sociodemographic questionnaire and validated 13 Hospital Depression and Anxiety Scale.and was distributed via the Internet. The results were 14 statistically analyzed. High school degree was the most commonly held education (46%), large city 15 was the most popular place of living (33%) and majority of the respondents have a full-time job 16 (53%). Only 19% of the respondents consult their doctor or pharmacists about taking CBD. On the 17 group of psychiatric patients, only 49% of respondents tell their psychiatrist about using the 18 compound. Psychiatrists should be aware of CBD use in their patients during their daily practice, as 19 CBD use can be found within people from all walks of life, and due to public interest, there is a need 20 for education and research on the efficacy and safety of CBD use for mental disorders.